Latitudinal and Seasonal Distribution of Particulate MSA over the Atlantic using a Validated Quantification Method with HR-ToF-AMS - Huang, S.; Poulain, L.; van Pinxteren, D.; van Pinxteren, M.; ZJ Wu; Herrmann, H.; Wiedensohler, A. (Environmental Science & Technology, 2017)
Methanesulfonic acid (MSA) has been widely used as a proxy for marine biogenic sources, but it is still a challenge to provide an accurate MSA mass concentration with high time resolution. This study offers an improved MSA quantification method using high resolution time of-flight aerosol mass spectrometer (HR-ToF-AMS). Particularly, the method was validated based on an excellent agreement with parallel offline measurements (slope = 0.88, R-2 = 0.89). This comparison is much better than those using previously reported methods, resulting in underestimations of 31-54% of MSA concentration. With this new method, MSA mass concentrations were obtained during 4 North/South Atlantic cruises in spring and autumn of 2011 and 2012. The seasonal and spatial variation of the particulate MSA mass concentration as well as the MSA to non-sea-salt sulfate ratio (MSA:nssSO(4)) over the North/South Atlantic Ocean were determined for the first time. Seasonal variation of the MSA mass concentration was observed, with higher values in spring (0.03 mu g m(-3)) than in autumn (0.01 mu g m(-3)). The investigation of MSA:nssSO(4) suggests a ubiquitous and significant influence of anthropogenic sources on aerosols in the marine boundary layer.
Keywords: aerosol mass-spectrometer; chemical-characterization; dimethyl sulfide; distributions; ENGINEERING; Environmental Sciences & Ecology; high-resolution; marine boundary-layer; mediterranean sea; organic-matter enrichment; sea-salt sulfate; size; sulfur-compounds